Candida parapsilosis complex - Moris, D. V. [UNESP]; Melhem, M. S.C.; Martins, M. A.; Mendes, R. P. [UNESP] (My University, 2013)
History. C. parapsilosis complex was first isolated by Ashford (1928) from the feces of a Puerto Rican patient with diarrhea, as a species of Monilia parapsilosis that was incapable of fermenting maltose and therefore reclassified as Candida parapsilosis by Langeron and Talice (1932). Ecology and Epidemiology. C. parapsilosis complex has an extensive distribution in nature, having been isolated from domestic animals, insects, soil, and marine environments. Known as a normal human commensal, it is also one of the most frequently isolated fungi from the subungual space of human hands. Its transient colonization of human integument is the basis of much debate as to whether or not C. parapsilosis is a pathogen or bystander in certain infections. C. parapsilosis complex has been reported as a contaminant of high concentration in glucose solutions and prosthetic material. Several nosocomial infections have been associated with its presence in contaminated hospital equipment via external sources such as medical devices or fluids, hands of health care workers, prosthetic devices, and can occur without prior colonization. C. parapsilosis complex is highly associated with the biofilms formation on various surfaces. Biofilms display a very complex threedimensional architecture, affecting the nutrient fluxes and waste products as well as the sensitivity of cells to antifungal drugs. Biofilms are already formed when C. parapsilosiscells grow in means containing high glucose and lipid concentrations, which is associated with the increased prevalence of bloodstream infections in patients receiving parenteral nutrition. C. parapsilosis complex is the second most common Candida species isolated from normally sterile body sites of hospitalized patients. It accounts for 15.5% of Candida isolates in North America, 16.3% in Europe, and 23.4% in Latin America, outranked only by C. albicans (51.5%, 47.8%, and 36.5%, respectively) and by C. glabrata (21.3%) in North America. Virulence factors. The pathogenesis of invasive candidiasis is facilitated by a number of virulence factors, mainly by adherence to host cells, biofilm formation, and secretion of hydrolytic enzymes - proteases, phospholipases, and lipases. Mycology. C. parapsilosis complex is formed by white and creamy colonies with variable morphology. It grows as oval cells or pseudohyphal filaments, but in contrast to C. albicans, it does not form true hyphae. Prior to 2005, C. parapsilosis complex was separated into groups I to III. Further genetic studies revealed sufficient differences that have led to the separation of the groups into closely related, distinct species: C. parapsilosis, C. orthopsilosis, and C. metapsilosis. The identification of C. parapsilosis complex is performed by conventional morphological and physiological methods and by molecular typing for identification of C. parapsilosis sensu stricto, C. orthopsilosis and C. metapsilosis species. Antifungal susceptibility. C. parapsilosis complex is usually susceptible to most antifungal compounds but decreased responsiveness to fluconazole and caspofungin was reported. It has also been suggested that C. orthopsilosis and C. metapsilosis could be more susceptible to amphotericin B and echinocandins than C. parapsilosis sensu stricto, which could affect therapeutic choices. Clinical manifestation. C. parapsilosis complex can cause several infections such as bloodstream infections, endocarditis, meningitis, onychomycosis, endophthalmitis, peritonitis, arthritis, otomycosis, vulvovaginitis and urinary tract infections.© 2013 Nova Science Publishers, Inc. All rights reserved.
Keywords: Antifungal susceptibility and clinical manifestation; C. Parapsilosis complex; Ecology; Epidemiology; Virulence factors